Carbon sheet, method for producing same, laminate, and power storage device

By designing a specific pore structure in the carbon sheet, the problem of insufficient growth inhibition performance of lithium dendrites in lithium-ion secondary batteries is solved, and the battery performance and cycling characteristics are significantly improved.

CN119421855APending Publication Date: 2025-02-11ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380052436.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-12
Filing Date
2023-08-02
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, there is room for further improvement in the lithium dendrites growth inhibition performance of lithium-ion secondary batteries, which affects the battery performance.

Method used

By introducing a specific pore structure into the carbon sheet, it is ensured that the pore distribution patterns of the carbon nanotubes and the carbon sheet meet specific conditions, thereby significantly improving the growth inhibitory performance of lithium dendrites.

Benefits of technology

Effective suppression of lithium dendrites is achieved, the battery performance of lithium-ion secondary batteries is improved, the cycle characteristics of the battery is extended, and the risk of short circuit is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a carbon sheet having excellent lithium dendrite growth suppression performance; and a method for producing the carbon sheet. Another purpose of the present invention is to provide: a laminate comprising a carbon sheet having excellent lithium dendrite growth suppression performance; and a power storage device. One of the present invention is a carbon sheet comprising carbon nanotubes, the carbon nanotubes and the carbon sheet each having pores, the distribution pattern of the pores satisfying prescribed necessary conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon sheet and a method for producing the same, as well as a laminate and an electricity storage device. Background Art

[0002] Carbon nanotubes (hereinafter, sometimes referred to as "CNTs") have attracted attention as materials with excellent electrical conductivity, thermal conductivity, electromagnetic wave shielding performance, and mechanical properties. In addition, focusing on these properties of CNTs, it has been proposed to manufacture a carbon nanotube film (hereinafter, sometimes referred to as "CNT film" or "carbon film"), which is sometimes called "bucker paper" and is formed by a plurality of CNTs gathered into a film, and to use the CNT film as a conductive sheet, a thermal conductive sheet, an electromagnetic wave absorbing sheet, etc.

[0003] Since CNT is a microstructure with a diameter of nanometer size, the operability and processability of a single individual are poor. Therefore, a scheme such as the following is proposed: a solution (CNT dispersion) in which CNT is dispersed is prepared, the solution is applied to a substrate, etc., and the aggregate of CNT contained in the CNT dispersion is formed into a film by removing components other than CNT to manufacture a carbon film. In recent years, in order to suppress the growth of lithium dendrites generated inside the battery when using a lithium ion secondary battery, attempts have been made to apply carbon films to electrodes of lithium secondary batteries (for example, refer to non-patent documents 1 and 2).

[0004] Prior art literature

[0005] Non-patent literature

[0006] Non-patent literature 1: Zhaowei Sun et al. “Robust Expandable Carbon Nanotube Scaffold for Ultrahigh-Capacity Lithium-Metal Anodes”, Advanced Materials, Germany, WILEY-VCH, 2018, 30, 1800884;

[0007] Non-patent document 2: Rodrigo V. Salvatierra et al. "Suppressing Li Metal Dendrites Through a Solid Li-Ion Backup Layer", Advanced Materials, Germany, WILEY-VCH, 2018, 30, 1803869. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] Here, from the viewpoint of improving the battery performance of lithium ion secondary batteries, there is room for further improvement in the performance of suppressing the growth of lithium dendrites in the above-mentioned conventionally proposed electrodes having a carbon film.

[0010] Therefore, an object of the present invention is to provide a carbon sheet having excellent lithium dendrite growth inhibition performance and a method for manufacturing the same.

[0011] Another object of the present invention is to provide a laminated body having carbon sheets and an electricity storage device that are excellent in the ability to suppress the growth of lithium dendrites.

[0012] Solutions for solving problems

[0013] The inventors have conducted in-depth research to achieve the above-mentioned purpose. Then, the inventors newly discovered that in a carbon sheet containing carbon nanotubes, the carbon nanotubes and the carbon sheet each have pores, and when the distribution morphology of these pores meets the required conditions, the growth inhibition performance of lithium dendrites is significantly improved, thereby completing the present invention.

[0014] That is, the object of the present invention is to advantageously solve the above-mentioned problems. [1] The carbon sheet of the present invention is characterized in that: it contains carbon nanotubes, and the data obtained by measuring the nitrogen adsorption amount of the above-mentioned carbon nanotubes are subjected to QSDFT (Quenched Solid Density Functional Theory; the distribution curve obtained by quenching solid density functional theory) analysis has a peak of more than 0.3cc / g in the pore diameter range of 0.9nm and less than 1.1nm, the vertical axis of the above distribution curve is the pore volume (Dv(logd)[cc / g]), and the horizontal axis is the pore diameter [nm]; the distribution curve obtained by measuring the nitrogen adsorption of the above carbon sheet has a peak of more than 1.5cc / g in the pore diameter range of less than 60nm, the vertical axis of the above distribution curve is the pore volume (DVp / dlogdp[cc / g]), and the horizontal axis is the pore diameter [nm]; the distribution curve obtained by measuring the mercury injection amount of the above carbon sheet has a peak of more than 2.0cc / g in the pore diameter range of more than 0.1μm and less than 10μm, the vertical axis of the above distribution curve is the pore volume (DVp / dlogdp[cc / g]), and the horizontal axis is the pore diameter [μm]. The carbon sheet that meets the specified properties has excellent lithium dendrite growth inhibition performance.

[0015] Here, in this specification, the above-mentioned properties of the carbon nanotubes and carbon sheets can be measured by the methods described in the examples, respectively.

[0016] [2] In addition, in the carbon sheet of [1], the carbon nanotubes preferably contain 50% by mass or more of single-walled carbon nanotubes. If 50% by mass or more of the carbon nanotubes contained in the carbon sheet are single-walled carbon nanotubes, the lithium dendrite growth inhibition performance of the carbon sheet can be further improved.

[0017] [3] In addition, in the carbon sheet of [1] or [2], it is preferred that the carbon sheet has a porous structure with a number average diameter of 50 nm to 200 nm on its surface when subjected to charge and discharge treatment. If a porous structure with a number average diameter of 50 nm to 200 nm is formed on the surface of the carbon sheet after charge and discharge treatment, the carbon sheet can further improve its performance in inhibiting the growth of lithium dendrites.

[0018] [4] In addition, the present invention aims to advantageously solve the above-mentioned problems. The laminate of the present invention is a laminate of a separator and the carbon sheet described in any one of [1] to [3]. When the laminate of the present invention is used in a storage device using a lithium-containing material, it has excellent performance in suppressing the growth of lithium dendrites.

[0019] [5] In addition, the present invention aims to advantageously solve the above-mentioned problems. The power storage device of the present invention is characterized in that it comprises an electrode and a separator, the electrode comprises a lithium-containing active material, and the carbon sheet described in any one of [1] to [3] is interposed between the electrode and the separator. The power storage device of the present invention has excellent performance in suppressing the growth of lithium dendrites.

[0020] [6] In addition, the power storage device of the present invention described in [5] is characterized in that after charge and discharge, a porous structure having a number average diameter of 50 nm to 200 nm is formed on the surface of the carbon sheet. The power storage device has excellent performance in suppressing the growth of lithium dendrites.

[0021] [7] In addition, the present invention aims to advantageously solve the above-mentioned problems. The method for manufacturing a carbon sheet of the present invention is characterized in that it includes: a step of dispersing a mixture of carbon nanotubes and a solvent to obtain a carbon nanotube dispersion, wherein the carbon nanotubes have a peak of 0.3 cc / g or more in the pore diameter range of 0.9 nm or more and 1.1 nm or less in the distribution curve obtained by QSDFT analysis of the data obtained by measuring the nitrogen adsorption amount, and the vertical axis of the distribution curve is the pore volume (Dv (logd) [cc / g]) and the horizontal axis is the pore diameter [nm]; and a step of removing the solvent from the carbon nanotube dispersion to form a carbon sheet. According to the method for manufacturing a carbon sheet, a storage device with excellent lithium dendrite growth inhibition performance can be efficiently manufactured.

[0022] Effects of the Invention

[0023] According to the present invention, a carbon sheet having excellent performance in suppressing the growth of lithium dendrites and a method for manufacturing the same can be provided.

[0024] Furthermore, according to the present invention, it is possible to provide a laminated body having a carbon sheet and an electric storage device that are excellent in the performance of suppressing the growth of lithium dendrites. DETAILED DESCRIPTION

[0025] The embodiments of the present invention are described in detail below. The carbon sheet of the present invention can be more efficiently manufactured by the method for manufacturing the carbon sheet of the present invention. In addition, the power storage device of the present invention can be efficiently manufactured by the method for manufacturing the power storage device of the present invention.

[0026] (Carbon sheet)

[0027] The carbon sheet of the present invention contains carbon nanotubes (hereinafter, sometimes referred to as CNTs). The carbon nanotubes have a peak of 0.3 cc / g or more in the pore diameter range of 0.9 nm or more and 1.1 nm or less of the distribution curve obtained by QSDFT analysis of the data obtained by measuring the nitrogen adsorption amount, with the vertical axis being the pore volume (Dv (logd) [cc / g]) and the horizontal axis being the pore diameter [nm]. In addition, the carbon sheet of the present invention has a peak of 1.5 cc / g or more in the pore diameter range of 60 nm or less of the distribution curve obtained by (1) measuring the nitrogen adsorption amount, with the vertical axis being the pore volume (DVp / dlogdp [cc / g]) and the horizontal axis being the pore diameter [nm], and has a peak of 2.0 cc / g or more in the pore diameter range of 0.1 μm or more and 10 μm or less of the distribution curve obtained by (2) measuring the mercury injection amount, with the vertical axis being the pore volume (DVp / dlogdp [cc / g]) and the horizontal axis being the pore diameter [μm]. A carbon sheet containing CNTs satisfying such properties and having a porous structure satisfying the above (1) and (2) has excellent performance in inhibiting the growth of lithium dendrites. Although the mechanism is unclear, it is speculated that if the carbon sheet has a porous structure formed by pores of a specific size, the growth of dendritic crystals can be suppressed by capturing the precipitated lithium in the pores when the size is small. Furthermore, if the carbon sheet has excellent performance in inhibiting the growth of lithium dendrites, short circuits or deactivation of lithium due to the formation of lithium dendrites can be effectively suppressed in the power storage device, thereby improving the cycle characteristics of the power storage device. In addition, short circuits can occur due to damage to the separators of the power storage device caused by lithium dendrites.

[0028] <Carbon Nanotube>

[0029] The CNT contained in the carbon sheet of the present invention needs to meet the following conditions: the distribution curve obtained by QSDFT analysis of the data obtained by measuring the nitrogen adsorption amount, with the vertical axis being the pore volume (Dv (logd) [cc / g]) and the horizontal axis being the pore diameter [nm], has a peak of 0.3cc / g or more in the pore diameter range of 0.9nm or more and 1.1nm or less. Furthermore, from the viewpoint of forming a good porous structure in the carbon sheet and further improving the growth inhibition performance of lithium dendrites of the sheet, the size of the peak detected in the pore diameter range of 0.9nm or more and 1.1nm or less is preferably 1.5cc / g or less, more preferably 1.2cc / g or less, and even more preferably 0.9cc / g or less.

[0030] In addition, CNT is not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, preferably containing single-walled carbon nanotubes (single-walled CNT) as the main component. As a component other than single-walled CNT that can be contained in CNT, multi-walled carbon nanotubes (multi-walled CNT) can be cited. Here, the ratio of single-walled CNT to the overall mass of CNT is preferably 50% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and can also be 100% by mass. If the ratio of single-walled carbon nanotubes in the carbon nanotubes contained in the carbon sheet is 50% by mass or more, the growth inhibition performance of lithium dendrites of the carbon sheet can be further improved. In addition, when CNT includes multi-walled CNT, the number of layers of multi-walled CNT is preferably less than 5 layers.

[0031] Furthermore, the carbon purity of CNT is preferably 95.0% by mass or more, and more preferably 99.0% by mass or more. In addition, the upper limit of the carbon purity of CNT is not particularly limited, and may be, for example, less than 99.9999%.

[0032] The BET specific surface area of ​​CNT is preferably 500 m 2 / g or more, more preferably 600m 2 / g or more, preferably 2000m 2 / g or less, more preferably 1800m 2 / g or less, more preferably 1600m 2 / g or less. If the BET specific surface area is within the above range, the lithium dendrite formation inhibition performance of the carbon sheet can be further improved. In addition, in the present invention, "BET specific surface area" refers to the nitrogen adsorption specific surface area measured using the BET (Brunauer-Emmett-Teller) method.

[0033] CNT is not particularly limited, and can be manufactured using known CNT synthesis methods such as arc discharge method, laser ablation method, chemical vapor deposition method (CVD method). Specifically, CNT can be efficiently manufactured according to, for example, the following method (super growth (SuperGrowth) method; reference International Publication No. 2006 / 011655): a raw material compound and a carrier gas are supplied to a substrate having a catalyst layer for manufacturing carbon nanotubes on the surface, and when synthesizing CNT by chemical vapor deposition method (CVD method), a trace amount of oxidant (catalyst activating material) is present in the system, thereby dramatically improving the catalytic activity of the catalyst layer. In addition, the carbon nanotubes obtained by the super growth method are sometimes referred to as "SGCNT" below.

[0034] Furthermore, it is preferred that the t-curve obtained from the adsorption isotherm of CNTs has an upwardly convex shape.

[0035] Here, in a material having pores on the surface, the growth of the nitrogen adsorption layer is divided into the following processes (1) to (3). The slope of the t-curve changes according to the following processes (1) to (3).

[0036] (1) The process of forming a monomolecular adsorption layer of nitrogen molecules on the entire surface

[0037] (2) The formation of a multi-molecular adsorption layer and the accompanying capillary condensation filling process in the pores

[0038] (3) The process of forming a multi-molecular adsorption layer on the apparently non-porous surface where the pores are filled with nitrogen

[0039] Moreover, the t-curve, which is convex upward, is located on a straight line passing through the origin in a region where the average thickness t of the nitrogen adsorption layer is small, whereas when t increases, the curve is located at a position offset downward from the straight line. CNTs having this t-curve shape indicate that the ratio of the internal specific surface area of ​​the CNT to the total specific surface area is large, and that a plurality of openings are formed in the CNT. As a result, it is presumed that a porous structure satisfying the above (1) and (2) is easily formed in a carbon sheet formed using the CNT.

[0040] In addition, the inflection point of the t-curve of the CNT is preferably in the range of 0.2≤t(nm)≤1.5, more preferably in the range of 0.45≤t(nm)≤1.5, and further preferably in the range of 0.55≤t(nm)≤1.0. Regarding the CNT whose inflection point of the t-curve is in this range, when the CNT is used to prepare a dispersion liquid, the CNT is not easy to agglomerate in the dispersion liquid. As a result, good film forming properties can be achieved when forming a carbon sheet.

[0041] Here, the “position of the bending point” is the intersection of the approximate straight line A of the above-mentioned process (1) and the approximate straight line B of the above-mentioned process (3).

[0042] Furthermore, the ratio (S2 / S1) of the internal specific surface area S2 of the CNT obtained by the t-curve to the total specific surface area S1 is preferably 0.05 or more and 0.30 or less. Regarding CNTs whose S2 / S1 value is within this range, when the CNTs are used to prepare a carbon nanotube dispersion, the CNTs are less likely to aggregate in the dispersion. As a result, a carbon nanotube dispersion having excellent stabilization of the CNT network in the dispersion can be obtained.

[0043] Here, the total specific surface area S1 and the internal specific surface area S2 of CNT can be obtained from its t-curve. Specifically, first, the total specific surface area S1 can be obtained from the slope of the approximate straight line of the process (1), and the external specific surface area S3 can be obtained from the slope of the approximate straight line of the process (3). Then, by subtracting the external specific surface area S3 from the total specific surface area S1, the internal specific surface area S2 can be calculated.

[0044] The measurement of the CNT adsorption isotherm, the preparation of the t-curve, and the calculation of the total specific surface area S1 and the internal specific surface area S2 based on the analysis of the t-curve can be performed using, for example, a commercially available measuring device "BELSORP (registered trademark)-mini" (manufactured by BEL Corporation of Japan).

[0045] The average diameter of CNT is preferably 1 nm or more, preferably 60 nm or less, more preferably 30 nm or less, and further preferably 10 nm or less.

[0046] The average length of CNT is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more, and is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less.

[0047] When a carbon nanotube dispersion is prepared using CNTs having an average diameter and / or an average length within the above range, the CNTs are less likely to aggregate in the carbon nanotube dispersion, and a stabilized CNT dispersion can be prepared.

[0048] The carbon nanotubes may be in the form of a CNT aggregate. As the CNT in the form of a CNT aggregate, for example, a CNT aggregate that satisfies at least one of the conditions (1) to (3) described below can be used.

[0049] <<CNT aggregate>>

[0050] Here, as the CNT aggregate used when forming the carbon sheet, it is preferable to use a CNT aggregate that satisfies at least one of the following conditions (1) to (3).

[0051] (1) In a spectrum obtained by Fourier transform infrared spectroscopy analysis of a carbon nanotube dispersion obtained by dispersing a carbon nanotube aggregate into a bundle length of 10 μm or more, at a wave number greater than 300 cm -1 And 2000cm -1 At least one peak based on plasmon resonance of the carbon nanotube dispersion exists in the following range.

[0052] (2) For carbon nanotube aggregates, the maximum peak in the pore distribution curve representing the relationship between pore diameter and Log differential pore volume obtained by the Barrett-Joyner-Halenda method based on the adsorption isotherm of liquid nitrogen at 77K is in the range of pore diameter greater than 100 nm and less than 400 nm.

[0053] (3) The peak of the two-dimensional spatial spectrum of the electron microscope image of the carbon nanotube aggregate is at 1 μm. -1 Above and 100μm -1 At least one of the following ranges exists.

[0054] The above conditions (1) to (3) are described in detail respectively.

[0055] <<Condition (1)>>

[0056] Condition (1) stipulates that "for a carbon nanotube dispersion obtained by dispersing a carbon nanotube aggregate into a bundle having a length of 10 μm or more, in a spectrum obtained by Fourier transform infrared spectroscopy analysis, at a wave number greater than 300 cm -1 And 2000cm -1 At least one peak based on plasma resonance of the carbon nanotube dispersion exists in the following range". Here, as an optical property of CNT, the strong absorption property in the far-infrared region has been widely known. The strong absorption property in the far-infrared region is considered to be caused by the diameter and length of the CNT. In addition, the absorption property in the far-infrared region, more specifically, the relationship between the peak based on plasma resonance of CNT and the length of CNT, has been studied in detail in non-patent literature (T.Morimotoet.al., "Length-Dependent Plasmon Resonce in Single-Walled Carbon Nanotubes", pp 9897-9904, Vol.8, No.10, ACS NANO, 2014).

[0057] From the viewpoint of further improving the dendrite precipitation suppression performance of the obtained carbon sheet, in condition (1), the peak due to the plasmon resonance of CNT preferably exists at a wave number greater than 300 cm -1 And 2000cm -1 The following range is more preferably present at a wave number of 500 cm -1 Above and 2000cm -1 The following ranges are more preferably present at a wave number of 700 cm -1 Above and 2000cm -1 The following range.

[0058] In the spectrum obtained by Fourier transform infrared spectroscopy analysis of CNT aggregates, in addition to the relatively gentle peak due to plasmon resonance of CNT dispersion, there is sometimes a peak at a wave number of 840 cm -1 Nearby, 1300cm -1 Nearby and 1700cm -1 Sharp peaks can be confirmed near . These sharp peaks do not belong to the "peaks based on plasmon resonance of carbon nanotube dispersion" and each corresponds to infrared absorption from functional groups. More specifically, the wave number 840 cm -1 The sharp peak near the surface is due to the out-of-plane bending vibration of CH; wave number 1300 cm -1 The sharp peak near the ring is due to the stretching vibration of the epoxy three-membered ring; wave number 1700cm -1 The sharp peak near is due to the stretching vibration of C=O. -1 In the region of , in addition to the plasmon resonance, as mentioned in the above-mentioned non-patent literature by T. Morimoto et al., since a peak similar to the S1 peak is detected, the upper limit of the determination of the presence or absence of the peak based on the plasmon resonance of the CNT dispersion in condition (1) can be 2000 -1 cm or less.

[0059] Here, in condition (1), when obtaining a spectrum based on Fourier transform infrared spectroscopy, it is necessary to obtain a CNT dispersion by dispersing the CNT aggregate into a bundle length of 10 μm or more. Here, for example, a CNT aggregate, water, and a surfactant (such as sodium dodecylbenzenesulfonate) are mixed in an appropriate ratio and stirred for a predetermined time by ultrasonic waves, etc., thereby obtaining a dispersion in which a CNT dispersion having a bundle length of 10 μm or more is dispersed in water.

[0060] The bundle length of the CNT dispersion can be obtained by analyzing with a wet image analysis type particle size measuring device. The measuring device can calculate the area of ​​each dispersion based on the image obtained by photographing the CNT dispersion, and obtain the diameter of a circle having the calculated area (hereinafter, sometimes also referred to as ISO area diameter). Moreover, in this specification, the bundle length of each dispersion is defined as the value of the ISO area diameter thus obtained.

[0061] <<Condition (2)>>

[0062] Condition (2) stipulates that "the maximum peak in the pore distribution curve is in the range of pore diameter greater than 100nm and less than 400nm". The pore distribution of the carbon nanotube aggregate can be obtained based on the BJH method from the adsorption isotherm of liquid nitrogen at 77K. In addition, the peak in the pore distribution curve obtained by measuring the carbon nanotube aggregate is in the range of greater than 100nm, which means that in the carbon nanotube aggregate, there are gaps of a certain size between CNTs, and the CNTs are not in a state of excessively dense aggregation. In addition, the upper limit of 400nm is the measurement limit when using, for example, BELSORP-mini II as a measurement device.

[0063] Here, from the viewpoint of further improving the dendrite precipitation suppression performance of the obtained carbon sheet, the value of the Log differential pore volume in the maximum peak of the pore distribution curve of the CNT aggregate is preferably 2.0 cm 3 / g or above.

[0064] <<Condition (3)>>

[0065] Condition (3) stipulates that "the peak of the two-dimensional spatial spectrum of the electron microscope image of the carbon nanotube aggregate is at 1 μm -1 Above and 100μm -1 At least one of the following ranges exists". The sufficiency of this condition can be determined based on the following points. First, use an electron microscope (for example, a field emission scanning electron microscope) to magnify and observe the CNT aggregate to be determined (for example, 10,000 times), and obtain multiple (for example, 10) electron microscope images in a 1 cm square field of view. Perform fast Fourier transform (FFT) processing on the multiple electron microscope images obtained to obtain a two-dimensional spatial spectrum. The two-dimensional spatial spectrum obtained from each of the multiple electron microscope images is binarized to find the average value of the peak position that appears on the highest frequency side. When the average value of the peak position is within 1 μm -1 Above and 100μm -1If the peak is within the following range, it can be determined that condition (3) is satisfied. Here, as the "peak" used in the above determination, a clear peak obtained by performing an isolated point extraction process (i.e., the reverse operation of eliminating isolated points) is used. Therefore, when performing an isolated point extraction process, the peak at 1 μm -1 Above and 100μm -1 When a clear peak cannot be obtained within the following range, it can be determined that the condition (3) is not satisfied.

[0066] Here, from the viewpoint of further improving the dendrite precipitation suppression performance of the obtained carbon sheet, the peak of the two-dimensional spatial spectrum is preferably present at 2.6 μm. -1 Above and 100μm -1 Within the following range.

[0067] Furthermore, from the viewpoint of further improving the dendrite precipitation suppression performance of the obtained carbon sheet, the CNT aggregate preferably satisfies at least two of the above conditions (1) to (3), and more preferably satisfies all of the conditions (1) to (3).

[0068] <<Other properties>>

[0069] Furthermore, the CNT aggregate that can be used when producing the carbon sheet of the present invention preferably has the following properties in addition to the above conditions (1) to (3).

[0070] The tapped bulk density of the CNT aggregate is preferably 0.001 g / cm 3 Above and 0.2g / cm 3 CNT aggregates within this density range have excellent dispersibility and can be molded into various shapes because the bonding between CNTs is not excessively strengthened. 3 If the tapped bulk density of the CNT aggregate is 0.001 g / cm 3 The tapped bulk density refers to the apparent bulk density in a densely packed state after the powdered CNT aggregate is filled into a container and then tapped or vibrated to reduce the gaps between the powder particles.

[0071] The G / D ratio of the CNT aggregate is preferably greater than 1 and can be less than 5. It is believed that the single-walled CNTs of the CNT aggregate with a G / D ratio of less than 1 have low crystallinity and a lot of contamination such as amorphous carbon. In addition, in the Raman spectrum of CNT measured by a Raman spectrometer, a band called G band (1600 cm -1 Nearby) and D belt (1350cm-1 The G band is a vibration mode derived from the hexagonal lattice structure of graphite which is the cylindrical surface of the CNT, and the D band is a vibration mode derived from the amorphous portion.

[0072] In order to obtain a high specific surface area, it is desirable that the purity of the CNT aggregate be as high as possible. The purity described here refers to the carbon purity, which is a value indicating how much of the mass of the CNT aggregate is composed of carbon. There is no upper limit to the purity in terms of obtaining a high specific surface area, but it is difficult to obtain a CNT aggregate of 99.9999% by mass or more in manufacturing. When the purity is less than 95.0% by mass, it is difficult to obtain a CNT aggregate of more than 1000 m3 without opening treatment. 2 / g specific surface area. Furthermore, when metal impurities are contained and the carbon purity is less than 95.0 mass %, the metal impurities react with oxygen during the opening process and hinder the opening of the CNT, so that it becomes difficult to expand the specific surface area. From these aspects, the purity of the single-walled CNT is preferably 95.0 mass % or more.

[0073] The purity of the CNT aggregate satisfying at least any one of the conditions of (1) to (3) above can usually be 98.0% by mass or more, preferably 99.0% by mass or more, even without purification. There are almost no impurities mixed in the CNT aggregate, and the various properties of CNT can be fully utilized. The carbon purity of the CNT aggregate can be obtained by elemental analysis using fluorescent X-rays, thermogravimetric analysis (TGA), etc.

[0074] <<Method for producing CNT aggregate>>

[0075] The method for producing a CNT aggregate is not particularly limited, and the production conditions can be adjusted according to the desired properties. For example, a CNT aggregate satisfying at least any one of the above conditions (1) to (3) can be produced according to the method described in International Publication No. 2022 / 114235.

[0076] <Characteristics of Carbon Sheet>

[0077] <<Nitrogen adsorption and mercury intrusion>>

[0078] The carbon sheet of the present invention needs to satisfy specific conditions when measuring the nitrogen adsorption and mercury intrusion respectively. Specifically, the carbon sheet needs to have a peak of 1.5 cc / g or more in the pore diameter range of 60 nm or less in the distribution curve obtained by measuring the nitrogen adsorption, with the vertical axis being the pore volume (DVp / dlogdp [cc / g]) and the horizontal axis being the pore diameter [nm]. In addition, the lower limit threshold of the pore diameter at which the peak position appears in the distribution curve obtained by measuring the nitrogen adsorption is not particularly limited, but is preferably 1 nm or more.

[0079] In addition, the carbon sheet needs to have a peak of 2.0 cc / g or more in the pore diameter range of 0.1 μm to 10 μm on the distribution curve obtained by measuring the mercury injection amount, with the vertical axis being the pore volume (DVp / dlogdp [cc / g]) and the horizontal axis being the pore diameter [μm].

[0080] It is speculated that a carbon sheet whose measurement results of nitrogen adsorption and mercury penetration respectively meet the above-mentioned specific conditions can suppress the growth of dendrite-like crystals by capturing lithium precipitated when using a storage device having an electrode containing a lithium-containing active material into a small-diameter pore structure.

[0081] <<Porosity>>

[0082] The porosity of the carbon sheet is preferably 70% or more, more preferably 85% or more, and preferably 99% or less. If the porosity is above the above lower limit, the lithium dendrite growth inhibition performance of the carbon sheet can be further improved. In addition, if the porosity of the carbon sheet is below the above upper limit, the strength can be improved. In addition, the porosity of the carbon sheet can be measured according to the method described in the embodiment.

[0083] <<Film thickness of carbon sheet>>

[0084] The thickness of the carbon sheet is preferably 50 μm or more, preferably 250 μm or less, and more preferably 200 μm or less. The thickness of the carbon sheet can be measured, for example, using a film thickness meter (digital thickness meter "JAN-255", manufactured by Ozaki Seisakusho Co., Ltd.).

[0085] <<Porous structure after charge and discharge treatment>>

[0086] When the carbon sheet is subjected to charge and discharge treatment, it is preferred that the sheet surface has a porous structure with a number average diameter of 50 nm or more and 200 nm or less. The conditions of the charge and discharge treatment are described in detail in the examples of this application. The charge and discharge treatment refers to repeatedly charging and discharging the manufactured unused power storage device at a specified interval.

[0087] Furthermore, the carbon sheet preferably has a porous structure with a number average diameter of 50 nm or more and 200 nm or less on its surface after charge and discharge treatment. If a porous structure of this size exists on the surface of the sheet after charge and discharge treatment, the growth inhibition performance of lithium dendrites of the carbon sheet can be further improved.

[0088] The frequency of occurrence of porous structures with a number average diameter of 50 nm or more and 200 nm or less in the surface of the sheet after charge and discharge treatment is preferably 2 or more, more preferably 3 or more, further preferably 5 or more, and usually 100 or less, for each image taken with a magnification of 100,000 times using FE-SEM (field emission scanning electron microscope) according to the evaluation method described in the embodiments of the present invention. If the frequency of occurrence of porous structures with a number average diameter of 50 nm or more and 200 nm or less in the surface of the sheet after charge and discharge treatment is within the above range, the growth inhibition performance of lithium dendrites of the carbon sheet can be further improved. In addition, the size of an image used to determine the frequency of occurrence of a porous structure can be 1280 nm × 890 nm.

[0089] (Method for manufacturing carbon sheet)

[0090] The carbon sheet includes: a step of mixing carbon nanotubes satisfying specified properties with a solvent and dispersing the mixture to obtain a carbon nanotube dispersion (a carbon nanotube dispersion preparation step); and a step of removing the solvent from the carbon nanotube dispersion to form a carbon sheet (a film formation step). According to the manufacturing method of the present invention including the steps, the carbon sheet of the present invention can be efficiently manufactured.

[0091] Hereinafter, each step will be described.

[0092] <Carbon Nanotube Dispersion Liquid Preparation Process>

[0093] In the carbon nanotube dispersion preparation step, carbon nanotubes satisfying predetermined properties are mixed with a solvent and dispersed to obtain a carbon nanotube dispersion. As CNTs satisfying predetermined properties, the above-mentioned CNTs and CNT aggregates can be used.

[0094] <<Solvent>>

[0095] As a solvent, there is no particular limitation, and examples include: alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amide-based polar organic solvents such as N,N-dimethylformamide and N-methylpyrrolidone (NMP); aromatic hydrocarbons such as toluene, xylene, chlorobenzene, o-dichlorobenzene, and p-dichlorobenzene. These can be used alone or in combination of two or more. Among them, as a solvent for CNT dispersion, water, alcohols, or mixtures thereof are preferably used, and water is more preferably used. When water is used as such a solvent, when a carbon sheet manufactured using a carbon nanotube dispersion using the water is used in a storage device, the carbon sheet has good affinity with the electrolyte and can achieve improved device performance.

[0096] <<Carbon Nanotube Content Ratio>>

[0097] The content of the carbon nanotubes in the carbon nanotube dispersion is not particularly limited, but is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more from the viewpoint of dispersibility. In addition, from the viewpoint of dispersibility, the content of the carbon nanotubes in the carbon nanotube dispersion is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, and further preferably 1.0% by mass or less.

[0098] <<Total content of carbon nanotubes and solvent>>

[0099] From the viewpoint of minimizing the amount of impurities remaining in the formed carbon sheet, the carbon nanotube dispersion preferably contains no components other than carbon nanotubes and solvent as much as possible. Conversely, in the carbon nanotube dispersion of the present invention, it is preferred that carbon nanotubes and solvent account for the majority. Specifically, the total content of carbon nanotubes and solvent in the carbon nanotube dispersion of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and it is further preferred that the carbon nanotube dispersion of the present invention contains no components other than carbon nanotubes and solvent.

[0100] <<Dispersion Process>>

[0101] Furthermore, from the viewpoint of improving the properties of the obtained carbon sheet, when dispersing CNT in a solvent, it is preferred to implement a dispersion treatment using a medium-free high-speed stirring disperser in a manner that satisfies the following conditions. In addition, before the dispersion treatment, the CNT may be pre-dispersed in a solvent using a stirrer or the like.

[0102] When performing the dispersion treatment, the dispersion time is preferably 15 minutes or more, more preferably 20 minutes or more, further preferably 25 minutes or more, preferably 45 minutes or less, more preferably 40 minutes or less. If the dispersion time is within the above range, the growth inhibition performance of lithium dendrites of the carbon sheet can be further improved.

[0103] In addition, during the dispersion treatment, the stirring circumferential speed of the medium-free high-speed stirring disperser is preferably 18 m / sec or more, more preferably 20 m / sec or more, preferably 40 m / sec or less, and more preferably 38 m / sec or less. If the stirring circumferential speed of the medium-free high-speed stirring disperser is within the above range, the growth inhibition performance of lithium dendrites of the carbon sheet can be further improved, and the strength and porosity of the carbon sheet can be controlled.

[0104] <Film forming process>

[0105] In the film forming step, the solvent is removed from the CNT dispersion prepared in the CNT dispersion preparing step to form a carbon sheet into a film.

[0106] <<Film formation of carbon sheet by solvent removal>>

[0107] The step of removing the solvent from the CNT dispersion to form a carbon sheet can be performed, for example, using any of the following methods (A) and (B).

[0108] (A) A method in which a CNT dispersion is applied to a film-forming substrate and then the applied CNT dispersion is dried.

[0109] (B) A method of filtering a CNT dispersion using a porous film-forming substrate and drying the obtained filtrate.

[0110] The carbon sheet obtained by the above methods (A) and (B) corresponds to the carbon sheet obtained by peeling the above dried product from the above film-forming substrate.

[0111] [Film-forming substrate]

[0112] Here, the film-forming substrate is not particularly limited, and a known substrate can be used according to the application of the carbon sheet to be produced.

[0113] Specifically, as the film-forming substrate for applying the CNT dispersion in the above method (A), a resin substrate, a glass substrate, a metal substrate, etc. can be cited. Here, as a resin substrate, a substrate consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytetrafluoroethylene (PTFE), polyimide, polyphenylene sulfide, aromatic polyamide, polypropylene, polyethylene, polylactic acid, polyvinyl chloride, polycarbonate, polymethyl methacrylate, alicyclic acrylic resin, cycloolefin resin, triacetyl cellulose, etc. can be cited. In addition, as a glass substrate, a substrate consisting of common soda glass can be cited. As a metal substrate, a substrate consisting of aluminum, copper, etc. can be cited.

[0114] In the above method (B), examples of the film-forming substrate for filtering the CNT dispersion include filter paper, and porous sheets made of cellulose, nitrocellulose, alumina, resin, etc. In addition, as the above film-forming substrate, for example, a membrane filter can be used.

[0115] [Coating]

[0116] As a method for coating the CNT dispersion on the film-forming substrate in the above method (A), a known coating method can be adopted. Specifically, as a coating method, dipping, roller coating, gravure coating, blade coating, air knife coating, roller knife coating, die coating, screen printing, spray coating and gravure offset printing can be used.

[0117] [filter]

[0118] As a method for filtering the CNT dispersion using the film-forming substrate in the above method (B), a known filtering method can be adopted. Specifically, natural filtration, reduced pressure filtration, pressurized filtration, centrifugal filtration, etc. can be used as the filtering method.

[0119] [dry]

[0120] As a method for drying the CNT dispersion applied to the film-forming substrate in the above method (A) or the filtrate obtained in the above method (B), a known drying method can be adopted. Examples of drying methods include hot air drying, vacuum drying, hot roll drying, infrared irradiation, etc. The drying temperature is not particularly limited, usually room temperature to 200°C, and the drying time is not particularly limited, usually 0.1 to 150 minutes.

[0121] <<Post-processing of carbon sheets>>

[0122] In the method for producing a carbon sheet of the present invention, the carbon sheet formed in the film forming step may be arbitrarily cleaned.

[0123] In addition, the cleaning of the carbon sheet can be performed by flushing the impurities remaining in the carbon sheet with a solvent. As the solvent used for cleaning, there is no particular limitation, and the above-mentioned solvent that can be used as a solvent for the CNT dispersion can be used, preferably the same solvent as the solvent for the CNT dispersion. In addition, the contact between the carbon sheet and the solvent can be performed by immersing the carbon sheet in the solvent or applying the solvent on the carbon sheet. Furthermore, the cleaned carbon sheet can be dried using a known method.

[0124] In addition, in the method for manufacturing the carbon sheet of the present invention, the carbon sheet formed in the film forming step can be arbitrarily pressed to further increase the density. From the viewpoint of suppressing the reduction of properties caused by damage or destruction of CNT, the pressing pressure during the pressing is preferably less than 3 MPa, and it is more preferable not to perform the pressing.

[0125] (Laminated body)

[0126] The laminate of the present invention has the carbon sheet of the present invention and a spacer. More specifically, the laminate of the present invention has a carbon sheet adjacently arranged on at least one surface of the spacer. In addition, the laminate may be a laminate in which the carbon sheet is adjacently arranged relative to one main surface of the spacer, or a laminate in which the carbon sheet is adjacently arranged relative to two main surfaces (the front and back surfaces). There is no particular limitation on the spacer, and previously known spacers commonly used in lithium-ion secondary batteries and lithium-ion capacitors, all-solid-state batteries, air batteries, double-layer capacitors, etc. can be used. Moreover, since the laminate of the present invention has the carbon sheet of the present invention, when used in a storage device using a lithium-containing substance, the growth inhibition performance of lithium dendrites is excellent. Therefore, the device characteristics such as the cycle characteristics of the storage device can be improved.

[0127] (Electricity storage device)

[0128] The power storage device of the present invention comprises an electrode and a separator, wherein the electrode comprises a lithium-containing active material. Furthermore, the carbon sheet of the present invention is interposed between the electrode comprising the lithium-containing active material and the separator. In the power storage device of the present invention, the growth of lithium precipitated inside the device as the power storage device is used can be suppressed to form lithium dendrites. Therefore, the occurrence of short circuits caused by damage to the separator by lithium dendrites can be suppressed, and the device characteristics such as cycle characteristics are excellent.

[0129] The power storage device is not particularly limited, and examples thereof include lithium ion secondary batteries, lithium ion capacitors, all-solid-state batteries, air batteries, and electric double layer capacitors.

[0130] As electrodes and separators containing lithium-containing active materials capable of forming an electric storage device, conventionally known electrodes and separators can be used. An electric storage device generally has a structure in which two electrodes (for example, a positive electrode and a negative electrode) are separated from each other by a separator. In the electric storage device of the present invention, a carbon sheet needs to be interposed between the electrode containing lithium-containing active materials and the separator among the electrodes possessed by the electric storage device. If the carbon sheet is arranged in a manner satisfying this positional relationship, the growth of lithium dendrites can be effectively suppressed. In addition, as required, the carbon sheet may also be arranged between the electrode not containing lithium and the separator.

[0131] In addition, the method for creating the basic structure of the power storage device is not particularly limited, and a conventionally known manufacturing method can be used.

[0132] Example

[0133] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0134] In addition, in Examples and Comparative Examples, various measurements and evaluations were performed as follows.

[0135] <CNT properties>

[0136] <<(1) Fourier transform infrared spectroscopy analysis (FT-IR) of CNT aggregate>>

[0137] 100 g of water containing sodium dodecylbenzenesulfonate at a concentration of 1% by mass as a surfactant was added to 10 mg of the CNT aggregate, and the mixture was stirred at 45 Hz for 1 minute using an ultrasonic bath to obtain 100 ml of a dispersion of each CNT aggregate.

[0138] Each dispersion prepared as described above was diluted twice with a solvent of the same composition, added dropwise onto a silicon substrate, and dried. A spectrum was obtained using a Fourier transform infrared spectrometer to obtain the wave number (cm2) of the peak of CNT based on the plasma resonance. -1 ).

[0139] <<(2) Preparation of pore distribution curve (CNT aggregate)>>

[0140] For CNT aggregates of more than 10 mg, the adsorption isotherm was measured using BELSORP-miniII (manufactured by MicrotracBEL) at 77K using liquid nitrogen (adsorption equilibrium time was 500 seconds). As a pretreatment, vacuum degassing was performed at 100°C for 12 hours. Based on the adsorption amount of the adsorption isotherm, the pore distribution curve of each sample was obtained by the BJH method. Confirm whether there is a maximum peak in the pore distribution curve of the CNT aggregate in the range of pore diameter of more than 1 nm and less than 400 nm.

[0141] <<(3) Two-dimensional spatial spectrum peak (CNT aggregate)>>

[0142] For each CNT aggregate of the embodiment, 0.01 mg was placed on a carbon tape, and the excess CNT was blown away with a blower to make a sample, and observed with a field emission scanning electron microscope at 10,000 times, and 10 photos were taken under an arbitrarily extracted 1 cm square field of view. The 10 electron microscope images taken were fast Fourier transformed to obtain a two-dimensional spatial spectrum. Each of the obtained two-dimensional spatial spectra was binarized, and the peak position appearing on the outermost side (high frequency side) was calculated to obtain the average value. In addition, during the binarization process, for the values ​​obtained after the fast Fourier transform process, the values ​​exceeding 0.75 were set to 1, and the other values ​​were set to zero.

[0143] <<(4) QSDFT analysis of nitrogen adsorption measurement values ​​of CNT>>

[0144] A CNT aggregate of more than 10 mg was used as an analysis sample, and a fully automatic gas adsorption measurement device AS-iQ-C (manufactured by Anton Paar. Co.) was used to measure nitrogen at 77.3K. At this time, as a pretreatment, vacuum degassing was performed at 100°C for 3 hours. According to the adsorption amount of the adsorption isotherm obtained by measurement, the pore distribution curve of each sample was obtained by the BJH method. The analysis of the micropores of the pore distribution of the sample was implemented according to the slit / cylindrical pore analysis model of the QSDFT method. In addition, the analysis range of the pore diameter is greater than 0.5nm and less than 2nm. Then, the peak size (cc / g) present at a diameter of 0.966nm was obtained.

[0145] <<G / D ratio>>

[0146] The Raman spectrum of CNT was measured using a microscopic laser Raman spectrophotometer (Nicolet Almega XR manufactured by Thermo Fisher Scientific). -1 The intensity of the G band peak observed near 1340 cm -1 The intensity of the D-band peak observed near was used to calculate the G / D ratio.

[0147] <Properties of Carbon Sheet>

[0148] <<Mercury injection amount>>

[0149] The mercury intrusion amount was measured for the produced carbon sheet (AutoPore V9620; manufactured by Micromeritics). The obtained data were plotted to obtain a distribution curve with the vertical axis being the pore volume (DVp / dlogdp[cc / g]) and the horizontal axis being the pore diameter [μm]. In the pore diameter range of 0.0036μm or more and 200μm or less of the distribution curve, it was determined whether there was a peak with a pore volume of 2.0cc / g or more. The values ​​of the pore diameter [μm] at which the peak with a pore volume of 2.0cc / g or more appeared are shown in Table 1.

[0150] <<Nitrogen adsorption amount>>

[0151] For the prepared carbon sheet, the nitrogen adsorption amount was measured using a pretreatment device (BELPREP-vacII; manufactured by Microtrac Bayer) and a formal measurement (BELSORP-miniII; manufactured by Microtrac Bayer). The obtained data were plotted to obtain a distribution curve with the vertical axis being the pore volume (DVp / dlogdp[cc / g]) and the horizontal axis being the pore diameter [nm]. In the pore diameter range of 60nm or less of the distribution curve, it was determined whether there was a peak with a pore volume of 1.5cc / g or more. The values ​​of the pore diameter [nm] where the peak with a pore volume of 1.5cc / g or more appeared are shown in Table 1.

[0152] <<Porosity>>

[0153] The porosity of the carbon sheet was calculated according to the following formula.

[0154] Porosity = (1-film density [g / cm 3 ] / 1.3)×100

[0155] Film density [g / cm 3 ] = weight of carbon sheet [g] / (thickness of carbon sheet [cm] × area of ​​carbon sheet [cm 2 ])

[0156] Assume that the density of CNT is 1.3 g / cm 3 .

[0157] <Cycling characteristics>

[0158] The produced symmetrical battery cell was used for a cycle characteristic test according to the following procedure. The cycle characteristics were evaluated based on the time until a short circuit or deactivation occurred.

[0159] Low capacity cycle characteristics test

[0160] Charge and discharge current per unit area: 2.0[mA / cm 2 ]

[0161] Charge and discharge capacity per unit area: 2.0[mAh / cm 2 ]

[0162] High capacity cycle characteristics test

[0163] Charge and discharge current per unit area: 40[mA / cm 2 ]

[0164] Charge and discharge capacity per unit area: 120[mAh / cm 2 ]

[0165] As a result of the cycle characteristics test, the longer the time until a short circuit or deactivation occurs, the more the carbon sheet can improve the cycle characteristics of the battery cell.

[0166] <Porous structure after cycle characteristics test>

[0167] The symmetrical battery cell after testing the above-mentioned cycle characteristics was disassembled, immersed and cleaned once with battery-grade polycarbonate, immersed and cleaned twice with ethyl methyl carbonate, and vacuum dried at room temperature to obtain an observation sample. The surface of the carbon sheet in contact with the separator was observed with an electron microscope.

[0168] The carbon sheet surface was evaluated to have numerous porous structures with an average diameter of 50 nm or more and 200 nm or less.

[0169] As an electron microscope, FE-SEM (field emission scanning electron microscope) was used. The observation magnification was 100,000 times, and the electron microscope image was taken. The obtained electron microscope image was imported into the image analysis software ImageJ, and the diameter of the voids present in one image (1280nm×890nm) was measured. The frequency of occurrence of porous structures with a number average diameter of 50nm or more and 200nm or less in each image was evaluated according to the following criteria.

[0170] The frequency of voids with pore diameters of 50 nm or more and 200 nm or less in one image is 5 or more: Porous structure

[0171] The frequency of voids with a pore size of 50 nm or more and 200 nm or less in one image is less than 5 or none: No porous structure

[0172] In addition, in the symmetrical battery cell in the example, voids with a diameter of less than 50 nm and voids with a diameter of more than 200 nm were observed, but most of the voids had a diameter in the range of 50 nm to 200 nm.

[0173] On the other hand, in the symmetrical battery cell of the comparative example, no voids with a diameter of 200 nm or less were observed, and even if voids existed, their diameters exceeded 200 nm.

[0174] <Evaluation of Dendrite Precipitation Suppression Performance>

[0175] The symmetrical battery cell after the above cycle characteristics were tested was disassembled, washed once by immersion in battery-grade polycarbonate and twice by immersion in ethyl methyl carbonate, and dried under vacuum at room temperature to obtain a sample for observation. The surface of the carbon sheet in contact with the separator was observed by electron microscope. The electron microscope image was imported into the image analysis software ImageJ to confirm whether there were dendrites in the image.

[0176] <Synthesis of CNT>

[0177] The CNTs used in Examples 1 and 3 (hereinafter referred to as "CNT_A") were produced by a method in which a granular catalyst carrier was continuously transported by screw rotation while supplying a raw material gas in the CNT synthesis step. Specifically, a CNT aggregate was produced according to the method disclosed in Example 4 of International Publication No. 2022 / 114237.

[0178] The properties of the manufactured CNT aggregate are typical values, G / D ratio: 1.2, tapped bulk density: 0.02 g / cm 3 、CNT average length: 150μm、BET specific surface area: 600m 2 / g, average outer diameter: 4.0nm, carbon purity: 99.0% by mass. In addition, various properties of the obtained CNT aggregate were measured as described above. The results are shown in Table 1.

[0179] (Example 1)

[0180] <CNT dispersion preparation process>

[0181] A mixture of 2 g of the CNT_A obtained as described above and 1998 g of water as a solvent was dispersed using a dispersing mill (manufactured by Asada Iron Works Co., Ltd.) as a disperser under the conditions shown in Table 1 to prepare a CNT dispersion.

[0182] <Film forming process>

[0183] A vacuum filtration device with a membrane filter was used to perform vacuum filtration for more than 12 hours at 0.09 MPa. Then, the carbon sheet was peeled off from the carbon sheet / membrane filter and the peeled carbon sheet was subjected to vacuum heat treatment at 150°C for 12 hours to obtain a carbon sheet. The mass per unit area of ​​the obtained carbon sheet was 2 mg / cm 2 , film thickness: 100 μm. Various properties of the carbon sheet were evaluated. The results are shown in Table 1.

[0184] <Production of symmetrical battery cells>

[0185] A set of lithium layers with carbon sheets arranged on one side of a lithium layer (manufactured by Honjo Metal) with a thickness of 300 μm was prepared. They were arranged so that the carbon sheet side was in contact with a polyethylene spacer (thickness 20 μm, manufactured by W-SCOPE Co., Ltd.), and a stacked body stacked in the order of lithium layer-carbon sheet-spacer-carbon sheet-lithium layer was prepared. The stacked body was placed in a coin battery cell box with a diameter of 1.6 cm and housed together with an electrolyte. As an electrolyte, a LiPF6 solution with a concentration of 1M was used (solvent: a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 1 / 1 (volume ratio), additive: containing 5 volume% (solvent ratio) of fluoroethylene carbonate (manufactured by Aldrich)). Then, the upper cover of the coin battery cell was placed, and a manual hydraulic press for coin battery cell assembly (manufactured by MTI) was used to press and tighten it to prepare a symmetrical battery cell. The porous structure of the obtained symmetrical battery cell after charge and discharge treatment was determined as described above, and the low-capacity cycle characteristics were tested. Furthermore, the porous structure and the presence of lithium dendrite precipitation after the cycle characteristics test were determined. The results are shown in Table 1.

[0186] (Example 2)

[0187] In preparing the CNT dispersion, various operations, measurements and evaluations were performed in the same manner as in Example 1 except that SGCNT (product name "ZEONANOSG101", manufactured by Zeon Corporation) obtained by the super growth method was used as CNT. The results are shown in Table 1. The obtained carbon sheet had a film thickness of 150 μm.

[0188] In addition, the properties of SGCNT are as follows.

[0189] BET specific surface area: 1000m 2 / g;

[0190] Carbon purity: 99.5 mass % or more.

[0191] (Example 3)

[0192] The high-capacity cycle characteristics of the symmetrical battery cell produced in the same manner as in Example 1 were tested. In addition, the porous structure and the presence of lithium dendrite precipitation after the cycle characteristics test were determined for the symmetrical battery cell tested for high-capacity cycle characteristics. The results are shown in Table 1.

[0193] (Example 4)

[0194] The high-capacity cycle characteristics of the symmetrical battery cell produced in the same manner as in Example 2 were tested. In addition, the porous structure and the presence of lithium dendrite precipitation after the cycle characteristics test were determined for the symmetrical battery cell tested for high-capacity cycle characteristics. The results are shown in Table 1.

[0195] (Comparative Example 1)

[0196] When preparing the CNT dispersion, the product name "Tuball" (manufactured by Tuball Co., Ltd.) was used as CNT, and a symmetrical battery cell was prepared in the same manner as in Example 1. For the prepared symmetrical battery cell, the porous structure after the charge and discharge treatment was determined as described above, and the low-capacity cycle characteristics and high-capacity cycle characteristics were tested. Furthermore, the porous structure after the cycle characteristics test and the presence or absence of lithium dendrite precipitation were determined. The results are shown in Table 1.

[0197] (Comparative Example 2)

[0198] When preparing the CNT dispersion, the product name "K-nanos100T" (manufactured by KNANO GRAPHENE COMPANY) was used as CNT, and the symmetrical battery cell was prepared in the same manner as in Example 1. For the prepared symmetrical battery cell, the porous structure after the charge and discharge treatment was determined as described above, and the low-capacity cycle characteristics and high-capacity cycle characteristics were tested. Furthermore, the porous structure after the cycle characteristics test and the presence or absence of lithium dendrite precipitation were determined. The results are shown in Table 1.

[0199]

[0200] As can be seen from Table 1, in Examples 1 to 4, carbon sheets having excellent performance in suppressing the growth of lithium dendrites were obtained.

[0201] Industrial Applicability

[0202] According to the present invention, a carbon sheet having excellent performance in suppressing the growth of lithium dendrites and a method for manufacturing the same can be provided.

[0203] Furthermore, according to the present invention, it is possible to provide a laminated body having a carbon sheet and an electric storage device that are excellent in the performance of suppressing the growth of lithium dendrites.

Claims

1. A carbon sheet comprising carbon nanotubes, The distribution curve obtained by QSDFT analysis of the data obtained by measuring the nitrogen adsorption amount of the carbon nanotubes has a peak of 0.3 cc / g or more in the pore diameter range of 0.9 nm or more and 1.1 nm or less, wherein the vertical axis of the distribution curve is the pore volume (Dv (logd) [cc / g]) and the horizontal axis is the pore diameter [nm], The distribution curve obtained by measuring the nitrogen adsorption amount of the carbon sheet has a peak of 1.5 cc / g or more in the pore diameter range of 60 nm or less, wherein the vertical axis of the distribution curve is the pore volume (DVp / dlogdp[cc / g]) and the horizontal axis is the pore diameter [nm]. The distribution curve obtained by measuring the mercury injection amount of the carbon sheet has a peak of more than 2.0 cc / g in the pore diameter range of 0.1 μm to 10 μm, and the vertical axis of the distribution curve is the pore volume (DVp / dlogdp[cc / g]) and the horizontal axis is the pore diameter [μm].

2. The carbon sheet according to claim 1, wherein: The carbon nanotubes contain more than 50% by mass of single-walled carbon nanotubes.

3. The carbon sheet according to claim 1, wherein: When the carbon sheet is subjected to charge and discharge treatment, the surface of the sheet has a porous structure with a number average diameter of 50 nm to 200 nm. 4 . A laminate comprising a separator and the carbon sheet according to claim 1 .

5. A power storage device comprising an electrode and a separator, wherein the electrode comprises a lithium-containing active material, The carbon sheet according to any one of claims 1 to 3 is interposed between the electrode and the separator.

6. The power storage device according to claim 5, wherein: After charge and discharge, a porous structure having a number average diameter of 50 nm to 200 nm is formed on the surface of the carbon sheet.

7. A method for manufacturing a carbon sheet, wherein the carbon sheet comprises carbon nanotubes, the method comprising: A step of dispersing the mixture of the carbon nanotubes and the solvent to obtain a carbon nanotube dispersion, wherein the carbon nanotubes have a peak of 0.3 cc / g or more in a pore diameter range of 0.9 nm or more and 1.1 nm or less of a distribution curve obtained by performing QSDFT analysis on data obtained by measuring nitrogen adsorption, wherein the vertical axis of the distribution curve is pore volume (Dv (logd) [cc / g]) and the horizontal axis is pore diameter [nm]; and A step of removing the solvent from the carbon nanotube dispersion to form a carbon sheet.

Citation Information

Patent Citations

  • Carbon film

    WO2022114235A1